Successful Treatment of Brittle Diabetes Following Total Pancreatectomy by Islet Allotransplantation: A Case Report - Koh, Angela; Imes, Sharleen; Shapiro, Andrew Mark James; Senior, Peter A (JOP. Journal of the Pancreas, 2013)
Context Allotransplantation of islets can successfully treat subjects with type 1 diabetes complicated by severe hypoglycemia and erratic glycemic control. Insulin independence is often lost over time due to several factors, including recurrent autoimmunity. Brittle diabetes (frequent hypoglycemia and labile glycemic control) is common after pancreatectomy. This is ameliorated by auto-islet transplantation in pancreatectomized patients who have better glycemic control, even without insulin independence. Case report We herein report a case where islet allotransplantation was carried out in a patient who had undergone total pancreatectomy. Following two islet infusions, he became insulin independent with excellent glycemic control and remains so currently, more than four years after his second islet infusion. Side effects from immunosuppressive therapy were minimal. Discussion Islet allotransplantation can be considered in selected individuals post-pancreatectomy. The absence of autoimmunity may be advantageous for long term graft function relative to islet allotransplantation in type 1 diabetic recipients. Image: HYPO score and lability index.